DAMPAK POSITIF DISCOVERY LEARNING MODELS TERHADAP PENINGKATAN KEMAMPUAN DASAR BERHITUNG SISWA - Agus Supriyanto; Khamid Budiman; Sri Tutur Martaningsih (Jurusan Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2021)
Primary school students' numeracy skills require learning stages following student development. Ignorance of the formula with mastery of calculating material is an obstacle, especially in the Covid-19 pandemic conditions. Model discovery learning can apply to online learning conditions. The research goal is to improve numeracy skills through discovery learning models (MDL). We applied classroom action research with study subject grade IV students. MLD with the numeracy skill discuss in this research. The application of the research was two cycles. This study's data collection methods were observation and tests in observation sheets and test questions. Data analysis using descriptive qualitative and descriptive quantitative. The findings showed that the use of MLD could improve the numeracy skills of students of primary school. The development of the first cycle is the value of MDL implementation of 87% with the rata-rata value of the numeracy ability of students of 94 and the acquisition of the result of the second cycle is the value of the implementation of the MLD of 95% with the rata-rata of the numeracy ability of the students of 97. Increasing numeracy skills with the application of MLD can be applied to primary school students. The role of guidance and counselling teachers with primary school teachers in collaboration develops students' numeracy skills in the digital era.